Cart That Carried Martin - Eve Bunting (Watertown, United States Charlesbridge Publishing,U.S., 2018)
The strength and spirit of Dr. Martin Luther King, Jr. permeates this picture book about the funeral of Dr. King in Atlanta, Georgia, in 1968. Quiet, yet affecting, THE CART THAT CARRIED MARTIN is a unique tribute to the life of a man known world-wide for his outstanding efforts as a leader of the African-American Civil Rights Movement. Eve Bunting focuses on the funeral procession of Dr. King, beginning with the two men who found the cart to carry him through the streets of Atlanta. After painting it green, two mules named Belle and Ada are hitched to the cart where Dr. King's coffin is placed. Tens of thousands of mourners gather as the cart makes its way to Ebenezer Baptist Church, and then past the Georgia state capitol to Morehouse College. All the while, crowds of people pay their respects by singing songs of hope. Bunting's thoughtful, well-chosen words, coupled with Don Tate's soft colors provide the reader with a sense of hope and reverence, rather than the grief and despair one might expec
Keywords: Circle Time